Evaluation of the effects of indocyanine green administration dose and speed on blood concentration and fluorescence in thoracoscopic segmentectomy - Noriyuki Misaki; Kayoko Sato; Kaede Yamada; Naoya Yokota; Natsumi Matsuura; Toshiki Yajima (PLoS ONE, 2026)
Intravenous administration of indocyanine green (ICG) is commonly used for visualizing lungs along the intersegmental plane; however, its effectiveness can be limited, as poor fluorescence sometimes leads to suboptimal structural delineation. We aimed to evaluate the effects of ICG dose and injection speed on blood concentration and fluorescence intensity during thoracoscopic segmentectomy. This was a two-stage, single-center study involving 30 patients who underwent segmentectomy. In the first stage, the administration rate was fixed at 300 mL/h and the dose was investigated at 0.1 mg/kg (group L) and 0.2 mg/kg (group H). In the second stage, a rate of 900 mL/h (group F) was added to the dose determined in the first stage and the relationship between the dose, administration rate, and fluorescence was investigated. During the first stage, the blood concentration of ICG at the end of the marking was higher in group H; hence, the dose in group F was set to 0.2 mg/kg. In the subsequent analysis, evaluation was performed by comparing the three groups. The maximum blood concentration of ICG was significantly higher in group F (9.5 mg/L, p < 0.01) than in the other groups. There was no difference in the fluorescence intensity between the groups. The fluorescence intensity of group L at the end of the marking was low (123.4, p = 0.03). The intersegment plane was confirmed in all cases, and there was no difference in the marking rate between the groups. Although injection speed affected blood ICG concentration, it did not significantly enhance fluorescence intensity. The administered dose of ICG determined the duration of fluorescence. Results suggest a minimum ICG dose is required to sustain fluorescence, while excessively rapid injections may cause early threshold attainment. Clinically, maintaining blood ICG concentration within the 5–10 mg/L is best achieved with a relatively slow infusion rate of 300 mL/h. Clinical trial registry number: UMIN-CTR No UMIN000047255.